ZFR coordinates crosstalk between RNA decay and transcription in innate immunity - Nazmul Haque (Nature Portfolio, 2018)
Type I interferon signaling is critical for the control of infection. Here the authors show that zinc finger RNA-binding protein (ZFR) can control type I interferon responses, and that this control is itself regulated by distinct ZFR truncation patterns that differ between monocytes and macrophages.